Pengaruh karakteristik perusahaan terhadap tax avoidance - Saraswati, Fitri Dyah; Utami, Endang Sri (LPMP Imperium, 2023)
This study examines the impact of firm characteristics on the practice of tax avoidance. The primary objective of this study is to examine the impact of profitability, leverage, liquidity, and business size on the level of tax avoidance among coal mining firms that are publicly listed on the Indonesia Stock Exchange during the time frame of 2019 to 2022. The study employed a quantitative approach and utilized a research design focused on establishing causal relationships. The information utilized for this research is categorized as secondary data. To determine the sample size utilizing the purposive sampling method, 44 data points were collected in total. The study utilized a documentation-driven approach to gather data. Descriptive analysis of classical assumptions and multiple linear regression analysis were utilized to analyze the research data. The results of this research suggest that there is no statistically significant relationship between profitability and tax avoidance. Nonetheless, it has been determined that both leverage and liquidity exert a substantial impact on tax avoidance. Conversely, it seems that the size of firm as an entity does not exert a substantial influence on tax avoidance. Tax avoidance is manifestly influenced by the concurrent presence of profitability, leverage, liquidity, and corporate scale.